Unexpected internal hernia in a patient with small bowel obstruction: an old surgical axiom. Issue 5 (6th May 2021) - Bryce, Adam; McMurray, Chloe; Hussain, Amir
Abstract : An 85-year-old man with no previous laparotomies and no herniae presented with a small bowel obstruction. CT imaging did not suggest any obvious cause; however, a transition point at the terminal ileum was noted. At laparotomy, the small bowel was unexpectedly found to be obstructed through a tight anterior hiatal defect. No resection was required and the defect was closed. On retrospective review of the CT images, the herniated small bowel can clearly be seen anterior to the oesophagus and can also be appreciated as a retrocardiac air–fluid level on chest X-ray (initially felt to be a small type I hiatal hernia). Our case highlights the surgical axiom that in patients with small bowel obstruction with no scars and no herniae consideration should be given to an unusual or sinister cause.